2015
DOI: 10.1055/s-0035-1554643
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Maximal Lactate Steady State in Junior Soccer Players

Abstract: This study aimed to predict the velocity corresponding to the maximal lactate steady state (MLSS(V)) from non-invasive variables obtained during an incremental maximal running test (University of Montreal Track Test, UMTT) and to determine whether a single constant velocity test (CVT), performed several days after the UMTT, could estimate the MLSS(V). During a period of 3 weeks, 20 male junior soccer players performed: (1) a UMTT, and (2) several 20-min CVTs to determine MLSS(V) to a precision of 0.35 km·h(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 34 publications
7
19
2
1
Order By: Relevance
“…The MLSS is not a practical and accessible measure, especially in team sports such as soccer, because it involves several bouts at different speeds on different days, and this modality involves a high number of athletes [9,10]. Previously, the prediction of MLSS was conducted in soccer players by using invasive procedures or multiple trials procedures [12][13][14][15][16]. Additionally, the determination of MLSS in the current study was derived from a very specific pattern of exercise, similar in nature to soccer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MLSS is not a practical and accessible measure, especially in team sports such as soccer, because it involves several bouts at different speeds on different days, and this modality involves a high number of athletes [9,10]. Previously, the prediction of MLSS was conducted in soccer players by using invasive procedures or multiple trials procedures [12][13][14][15][16]. Additionally, the determination of MLSS in the current study was derived from a very specific pattern of exercise, similar in nature to soccer.…”
Section: Discussionmentioning
confidence: 99%
“…The submaximal estimates of MLSS derived from T-Car incremental test were: a) Heart rate deflection point (HRDP): defined as the intensity of transition of a linear (or quasi-linear) increase of HR to an non-linear increase in the HR, the point of deflection was defined by visual inspection [18]; b) Heart rate deflection point Dmax method (HRDPDmax): calculated by a third order polynomial regression, from the HR versus speed values. The two endpoints of the curve were connected by a straight line, and the most distant point of the curve to the line was considered as the HRDPDmax, only values of HR ≥ 140 bpm were used in this analysis [19]; c) Fixed percentage of 80.4 % of sPeak (80.4 %sPeak): determined by linear interpolation between two stages at speed equivalent to 80.4 % of T-Car sPeak [5]; d) Fixed percentage of HRmax of 90 % (90 %HRmax): determined by interpolation between two stages at HR equivalent to 90 % of HRmax [16,20]; and e) Fixed percentage of HRmax of 91.4 % (91.4 %HRmax): determined by interpolation between two stages at HR equivalent to 91.4 % of HRmax [21]. Originally, the 80.4 %sPeak and 91.4%HRmax were derived from a large sample size (n = 112) as the percentages of sPeak and HRmax, respectively, equivalent to HRDPDmax using the T-Car test [21], and the 90 %HRmax was used in previous studies [16,20].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding this statement was not evidence-supported. It seems therefore worth mentioning that the review overlooked studies where MLSSint was determined with a precision of 0.2-0.35 km h −1 without exceeding the typical number of trials required for MLSSint determination (Garcia-Tabar & Gorostiaga, 2018;Llodio, Garcia-Tabar, Sánchez-Medina, Ibáñez, & Gorostiaga, 2015;Llodio, Gorostiaga, Garcia-Tabar, Granados, & Sánchez-Medina, 2016). Moreover these studies demonstrated that 1-2 tests are enough to precisely estimate the MLSSint.…”
Section: Dear Editormentioning
confidence: 99%
“…Тие нашле дека испитувањето на анаеробниот праг во споменатите услови може да ги утврди субмаксималните физиолошки варијабли кај млади фудбалери. [11]. Се покажа дека испитувањето на оваа варијабла може да помогне во процесот на тренирање кај младите фудбалери.…”
Section: дискусијаunclassified